INHIBITORY TEST OF ETHANOL EXTRACT OF ARABICA COFFEE LEAVES (COFFE ARABICA L) AGAINST ESCHERICHIA COLI BACTERIA - Safrida, Yuni Dewi; Hardiana, Hardiana; Gusrianti, Erni (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Arabica coffee is a plant that is believed to be used as a medicine, namely as a treatment for diabetes and as an immune system. Arabica coffee leaves contain chemical compounds of flavonoids, saponin alkaloids and polyphenols which act as antibacterial. This study, tested the inhibition of the ethanolic extract of arabica coffee leaves (Coffea arabica L.) against the growth of Eschrichia coli bacteria. The aims of this study was to determine the inhibitory ability of the ethanolic extract of arabica coffee leaves on the growth of Escherichia coli bacteria with a concentration of 20%, 40%, 60%, 80 % and 100%. Methods: The method used is the disk diffusion. Arabica coffee leaf extract was obtained by maceration using 96% ethanol solvent with Amoxicillin used as a positive control. This research was conducted at the AKAFARMA Laboratory from 18 to 25 June 2020. Result: The results showed that the ethanolic extract of arabica coffee leaves was able to inhibit the Escherichia coli bacteria. With the resulting inhibition zone diameter at concentrations of 20% 10 mm, 40% 12 mm, 60% 13 mm, 80% 14 mm and 100% 17 mm. Recommendation: This test needs to be carried out on other bacteria such as Streptococcus mutans and Stapylococcus aureus and others and it is necessary to test other parts such as flowers, seeds and fruit flesh using different methods.